Невербальні засоби у науковій комунікації викладачів та студентів - Науменко, Наталія Валентинівна; Расулова, Аліна (My University, 2019)
У статті проаналізовано найчастіше застосовувані у практиці спілкуванні викладачів і студентів НУХТ невербальні засоби, які, поряд із вербальними, забезпечують повноцінний обмін інформацією, настільки потрібний для організації спільної діяльності. Показано, що врахування всіх чинників невербального спілкування надзвичайно важливе у професійному спілкуванні, зокрема у сфері вищого навчального закладу; з’ясовано, що від того, наскільки добре суб'єкти переговорних процесів – навчальних занять, ділових засідань, наукових конференцій – володіють різними нюансами невербального спілкування, може залежати успішний його результат. The article gives an analysis of the non-verbal means to be frequently used in communication between teachers and students of National University of Food Technologies. There were observed the ways to use and to alternate the non-verbal means during several forms of scientific communication like a lecture (including the open), department meetings and monitors' meetings ('starostats,' in Ukrainian), and conferences to make up the notion about the working atmosphere at the university as a whole. As it is well-known, the non-verbal means of communication sometimes are more informative than those verbal; however, they altogether provide the fruitful informational exchange which is cardinally necessary for the mutual work. The authors of the article prove that consideration of all the factors of non-verbal communication is very important for effective professional activity, especially within the institution of higher education. There is particularly shown that the ability of the participants of negotiation processes (academic classes, business meetings, and scientific conferences) to deal with the non-verbal means can surely condition their successful results.
Keywords: кафедра іноземних мов професійного спрямування; викладач ЗВО; nonverbal communication; невербальне спілкування; технічні засоби навчання